2000
DOI: 10.1117/12.395451
|View full text |Cite
|
Sign up to set email alerts
|

SPIFFI image slicer: revival of image slicing with plane mirrors

Abstract: SPIFFI (SPectrometer for Infrared Faint Field Imaging) is the integral field spectrograph of the VLT-instrument SINFONI (SINgle Far Object Near-infrared Investigation). SINFONI is the combination of SPIFFI with the ESO adaptive optics system MACAO (Multiple Application Concept for Adaptive Optics) offering for the first time adaptive optics assisted near infrared integral field spectroscopy at an 8 m-telescope. SPIFFI works in the wavelength ranger from 1.1 to 2.5 tm with a spectral resolving power ranging fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…No glue is used in the assembly. A detailed description of the design and the manufacturing technique can be found in [11,13]. The problems in the manufacturing of the slicer are mainly in the process of cleaning and handling.…”
Section: Image Slicermentioning
confidence: 99%
See 1 more Smart Citation
“…No glue is used in the assembly. A detailed description of the design and the manufacturing technique can be found in [11,13]. The problems in the manufacturing of the slicer are mainly in the process of cleaning and handling.…”
Section: Image Slicermentioning
confidence: 99%
“…The working principle of the integral field spectrometer SPIFFI is copied from its precursor 3D [10]. Both instruments are built around an image slicer with plane mirrors [11]. However, SPIFFI is fully cryogenic, including the image slicer, and the number of spatial pixels is four times as large.…”
mentioning
confidence: 99%
“…Through further study on typical 3-mirror design, it's indicated that big fold angle on spherical mirror is the primary reason to degrade image quality, especially spherical pupil mirror, see Figure 4. Flat pupil mirrors used in some 2-mirror designs don't cause this serious degradation, for example, Keck II -KCWI [4] and VLT -SPIFFI [6]. And the design of Hale -SWIFT [7] and VLT -MUSE [8] also verifies that it's feasible to compensate the imaging function deletion of flat pupil mirror by locating slit mirror at a specific position.…”
Section: Optical Designmentioning
confidence: 99%
“…We could reproduce this behaviour by varying the pupil position on the grating. One possible source of movement of the pupil position is the image slicer, which is described in detail in Tecza et al (2000). 18 A torsional deformation of a slicer mirror with a measured amplitude of 2 HeNe fringes (close to what could be expected based on measurements of the slicer mirrors; see Eisenhauer et al (2003) 1 for an example of a slicer interferogram) would result in the pupil shifting on the grating by approximately ± 10 mm, which is nearly an entire period of the grating deformation function.…”
Section: J-bandmentioning
confidence: 99%
“…One possible source of movement of the pupil position is the image slicer, which is described in detail in Tecza et al (2000). 18 A torsional deformation of a slicer mirror with a measured amplitude of 2 HeNe fringes (close to what could be expected based on measurements of the slicer mirrors; see Eisenhauer et al (2003) 1 for an example of a slicer interferogram) would result in the pupil shifting on the grating by approximately ± 10 mm, which is nearly an entire period of the grating deformation function. Both the asymmetry in the 25 mas pixel scale line profiles and the variation in line profile along a slitlet can be explained with a shift in the pupil (due to, for example, a torsion in the slicer mirrors) in combination with the grating deformation.…”
Section: J-bandmentioning
confidence: 99%